UMP shares newfound innovation in wastewater treatment - UMP, PNC
Universiti Malaysia Pahang (UMP) shares newfound innovation in wastewater treatment when its lecturer Abdul Syukor Abdul Razak from the Faculty of Civil Engineering & Earth Resources (FKASA) discovered a method to treat domestic wasterwater using several organic plants to rid of contaminants.